SUBSTITUSI SEMEN DENGAN LIMBAH MARMER TERHADAP KUAT TEKAN MORTAR - Nanang Dalil Herman; Aida Fitriani S; Istiqomah Istiqomah (Kokoh, 2021)
This study will discuss the effect of cement substitution with marble waste against the compressive strength of mortar. marble waste which is used as research, of course, has been selected according to the size of the required. In this study, the attitude waste used from the Padalarang area, West Bandung Regency. The research method used is the experimental method with manufacture of test objects in the laboratory which are then carried out testing on the 3rd, 7th, 14th, 21st and 28th days. On research. This is made of 4 different types of mixtures as many as 3 pieces per type. As a comparison, ordinary mortar was also made. Design Method mortar using SK SNI M-111-1990-03 with compressive strength mortar the planned amount is 52 kg/cm2. Based on the mortar compressive strength test, it can be seen that mortar with a mixture of waste means decreased compressive strengthÂ Keywords: Cement, Compressive Strength, Marble Waste, Mortar, Subsitution